Community Organization-Based Literacy Empowerment for Women to Support Acceleration of Indonesian Digital Civilization Index - Andi Windah; Ida Nurhaida; Lusmeilia Afriani; Budiharjo; Nina Yudha Aryanti (Peneliti Teknologi Teknik Indonesia, 2023)
Indonesia has attained the bottommost rank in the global ranking of the World Digital Civility Index (DCI). The state renders female administrators and members of community-based organizations susceptible to deceitful machinations and exposure to impolite behavior within the realm of digital media, unless they possess the requisite competencies in digital literacy. This community service endeavors to impart digital literacy skills, particularly to female administrators and members of Perkumpulan Urang Banten (PUB) at Lampung Province. The purpose of this is to enable female administrators and PUB Lampung to derive the utmost benefit from media utilization, and to exercise discernment and discretion in selecting information. During the community service, most of participants have experienced significant improvements in their knowledge and practical skills. The program has equipped them with understanding of various hoaxes and online surfing ethics, enabling them to navigate the digital landscape with confidence. Furthermore, they have acquired skills in becoming responsible digital citizenship and protect themselves in the digital world. The community service has truly been transformative, empowering participants with the necessary knowledge and practical skills to thrive in an increasingly digital society. By doing so, thereby aiding the advancement of the DCI for the Indonesian populace.